Utilizando programação orientada a aspectos no projeto de sistemas hardware desenvolvidos com SystemC - Medeiros, Sergio Queiroz de (2006)
New programming language paradigms have commonly been tested and eventually incorporated into hardware description languages. Recently, aspect-oriented programming (AOP) has shown successful in improving the modularity of object-oriented and structured languages such Java, C++ and C. Thus, one can expect that, using AOP, one can improve the understanding of the hardware systems under design, as well as make its components more reusable and easier to maintain. We apply AOP in applications developed using the SystemC library. Several examples will be presented illustrating how to combine AOP and SystemC. During the presentation of these examples, the beneﬁts of this new approach will also be discussed